The Effectiveness of Jump Rope and Plyometrics on Improving Freestyle Swimming Speed - Rio Chandra Nugraha; Rizal Ahmad Fauzi; Aam Ali Rahman (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
The low freestyle swimming speed in elementary school students is influenced by less than optimal leg muscle strength, explosive power, and leg movement coordination. In addition, the training methods used are still less varied so that the most effective method in increasing freestyle swimming speed is not yet known. This study aims to determine the effectiveness of Jump Rope and plyometric training on increasing freestyle swimming speed. This study uses a quantitative approach with a quasi-experimental design. The research sample consisted of 15 students who were divided into a Jump Rope group, a plyometric group, and a control group. The data collection technique used a freestyle swimming speed test through a pretest and posttest. Data analysis was carried out using normality tests, homogeneity tests, and hypothesis testing using One Way ANOVA. The results showed that all groups experienced an increase in freestyle swimming speed. The Jump Rope and plyometric groups showed a greater increase than the control group, with a higher average increase. However, the results of the ANOVA test showed no significant difference between the treatment groups. In conclusion, both Jump Rope and plyometric training are equally effective in increasing freestyle swimming speed, but there is no significant difference in effectiveness between the two.